(3GdJMQjQ hGdJMHjQ aj GdJaSjQs - (3LeGd GdOjf CHh YHO Gddg eMeO Hf SdjeGf Hf GdMSf GdHdNj GdebOSj GdMfaj, GHf GdfbjH,J (B698 (3g` s
(3ChdgG (B:s
(3jHJOF ef ShQI GdeOKQ s
(3BNQgG (B:s
(3MJi BNQ GdbQBf s
(3LRA efgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B150s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B26 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B358s
Keywords: (3GdJaSjQ hYdhe GdbQBfs